Mannerheim : president, soldier, spy - Clements, Jonathan, 1971- (Haus Publishing, 2012)
""An exemplary and generously illustrated account; it incorporates new historical material, and he describes the journey as if he had been there.""--The Times Literary Supplement Gustaf Mannerheim was one of the greatest figures of the twentieth century. He spent two years undercover in Asia as a spy, escaped the Bolsheviks in 1917, lead the anti-Russian forces in the civil war and later, during Finland's darkest hour, lead the defense of his country against the impossible odds of the Winter War. Mannerheim is a fascinating appraisal of an adventurer and explorer who would go on to forge a ne.